ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGRAJIN BATOK KELAPA UKIR DI DESA TAMPAKSIRING, GIANYAR - Pratama, Made Fernanda; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323]DO - 10.24843/EEP.2022.v11.i08.p11, 2022)
One sector that has a role in the process of economic development is the industrial sector. The purpose of this research is to analyze 1) the influence of labor, raw materials, technology and production on the income of carving coconut shell craftsmen in Tampak Siring Village, Gianyar. 2) the direct influence of labor, raw materials, technology and production on income in the carved coconut shell industry. 3) the indirect effect of labor, raw materials and technology on income through production in the carved coconut shell industry. 4) modern technology has a significant positive effect on income. 5) labor, raw materials and production have an indirect effect on income through production. The sample used was 72 craftsmen, using a saturated sampling technique. The analysis technique used is path analysis. The results showed 1) modern technology has a significant positive effect on production. 2) Labor and raw materials have a significant positive effect on production. 3) Labor, raw materials, and production have a significant positive effect on income. 4) Modern technology has a significant positive effect on income. 5) Labor, raw materials and production have an indirect effect on income through production.   Keywords: labor, raw materials, technology, production. .